If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2(3x + -9y + 5) + (-9) = 12x + -18y + 1 Reorder the terms: 6x + 2(5 + 3x + -9y) + (-9) = 12x + -18y + 1 6x + (5 * 2 + 3x * 2 + -9y * 2) + (-9) = 12x + -18y + 1 6x + (10 + 6x + -18y) + (-9) = 12x + -18y + 1 6x + 10 + 6x + -18y + -9 = 12x + -18y + 1 Reorder the terms: 10 + -9 + 6x + 6x + -18y = 12x + -18y + 1 Combine like terms: 10 + -9 = 1 1 + 6x + 6x + -18y = 12x + -18y + 1 Combine like terms: 6x + 6x = 12x 1 + 12x + -18y = 12x + -18y + 1 Reorder the terms: 1 + 12x + -18y = 1 + 12x + -18y Add '-1' to each side of the equation. 1 + 12x + -1 + -18y = 1 + 12x + -1 + -18y Reorder the terms: 1 + -1 + 12x + -18y = 1 + 12x + -1 + -18y Combine like terms: 1 + -1 = 0 0 + 12x + -18y = 1 + 12x + -1 + -18y 12x + -18y = 1 + 12x + -1 + -18y Reorder the terms: 12x + -18y = 1 + -1 + 12x + -18y Combine like terms: 1 + -1 = 0 12x + -18y = 0 + 12x + -18y 12x + -18y = 12x + -18y Add '-12x' to each side of the equation. 12x + -12x + -18y = 12x + -12x + -18y Combine like terms: 12x + -12x = 0 0 + -18y = 12x + -12x + -18y -18y = 12x + -12x + -18y Combine like terms: 12x + -12x = 0 -18y = 0 + -18y -18y = -18y Add '18y' to each side of the equation. -18y + 18y = -18y + 18y Combine like terms: -18y + 18y = 0 0 = -18y + 18y Combine like terms: -18y + 18y = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 1.25(20x+12)=-35 | | 5/13×t=-9 | | -20=25+3x | | 6/.02 | | h+367=285 | | (3x-9)/5=6 | | 2b^2-2b-5=0 | | -8x+1.4=9.4 | | x/1-9=-9 | | (5x-6)(x+10)=0 | | 75q=3756 | | -6x-6-7=-13 | | -2(x-9)=-34 | | 8b=96 | | 4k-5k-4k= | | 17g=981 | | 4x^3-2x^3= | | -5=q^7 | | 30=12x-4+10x-10 | | -14x=-336 | | 3x-9/5=6 | | .75z+6= | | 3(y-4)=(3y-5-4y)-(2-5y+10) | | 6.6g+4=4.6g+8 | | 75=3x+2+10x-5 | | 1/3-4/x=2-3/2x | | 7x-10+28+2x=-5 | | 5b=2.000 | | Y=2x^4+18x^3+40x^2+24x | | y+708=1179 | | (6gk)/(3k^2) | | 2w-3= |